Estimated Evaluations of Bring Your Own Device (BYOD) ‎Technology Implementation in Gaza Strip Secondary Schools - ‎Difficulties of Implementation From the Teacher’s Perspective - Abed Al-Moniem, Rania (Jordan Journal of Educational Sciences, 2019)
This study aimed to identify the estimated evaluations of secondary school teachers for employing the BYOD technology, in secondary education in Gaza and the difficulties facing the use of this technique, and then it proposed a model for the use of technology in education. The researcher used a descriptive analytical method. The study sample consisted of (100) secondary teachers, selected randomly, from the secondary school teachers in Gaza Governorate. Two scales were constructed; one for the teachers' assessments of the use of BYOD technology in secondary education, and the other for the implementation of BYOD technology in secondary education, from the perspective of secondary school teachers. The study concluded that there is interest by the teachers in modern technologies, despite the lack of requirements to use this technology in education. Moreover, the study concluded the most important difficulties to the use of this technology in education. Based upon that, the researcher developed a proposed scenario for employing BYOD technology in secondary education.